1998
DOI: 10.1002/(sici)1521-4184(199802)331:2<72::aid-ardp72>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Properties of New Adamantane Derivatives. Design, Synthesis, and Biological Evaluation

Abstract: A series of adamantane‐containing molecules consisting of two lipophilic centers which are linked by different bridges (oxime esters, oxime ethers, amides, and symmetric alcohols), were designed and synthesized as anti‐inflammatory agents. Their anti‐inflammatory activity was evaluated as their ability to inhibit phlogistic‐induced mouse paw edema. Some of the tested compounds exhibited activity comparable to that of diclofenac, others had a weaker activity, while some oxime esters proved to enhance the inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…To date, seven adamantane derivatives have been applied in clinical usage to treat acne vulgaris [1], Alzheimer's disease [2], as an anti-viral [3][4][5][6][7] and for type-2 diabetes [8][9][10], while the others are in development as potential therapeutics for iron overload disease, neurological conditions, malaria, tuberculosis and cancers [11]. Previous studies on adamantyl-based compounds revealed their antioxidant and anti-inflammatory properties [12][13][14]. As a reactive oxygen species, hydrogen peroxide is generated as a by-product of biological reaction.…”
Section: Introductionmentioning
confidence: 99%
“…To date, seven adamantane derivatives have been applied in clinical usage to treat acne vulgaris [1], Alzheimer's disease [2], as an anti-viral [3][4][5][6][7] and for type-2 diabetes [8][9][10], while the others are in development as potential therapeutics for iron overload disease, neurological conditions, malaria, tuberculosis and cancers [11]. Previous studies on adamantyl-based compounds revealed their antioxidant and anti-inflammatory properties [12][13][14]. As a reactive oxygen species, hydrogen peroxide is generated as a by-product of biological reaction.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main categories of antiherpes agents presently used in chemotherapy are adamantane derivatives (amantadine, 1-aminotricyclo [3,3,1,13,7]decane, rimantadine, a-methyltricyclo [3,3,1,13,7]decane-1-methanamine, and memantine, 3,5-dimethyl-tricyclo- [3,3,1,13,7]decan-1-amine) that effectively suppress virus adsorption [1,2] and therefore are also utilized for treatment of the influenza A virus infection and prophylaxis [3,4]. This potent antiviral activity together with the significant neuroprotective properties of the N-methyl-D-aspartate (NMDA) antagonist memantine has stimulated tremendous interests in separation and determination of adamantane derivatives in clinical chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Oxime esters have been found in various areas. For example, a wide range of biologically active compounds with anticancer, 1 anti-inflammatory, 2 antifungal, 3 antioxidant and antimicrobial 4 activities contain oxime ester moieties. Additionally, oxime esters are an important scaffold for many organic synthesis processes such as C–C bond cleavage, 5 cyanoalkylation, 6 hydroesterification, 7 cross coupling, 8 sulfonylamination, 9 and cyclization.…”
Section: Introductionmentioning
confidence: 99%